KEPEMIMPINAN PENDETA YANG ADAPTIF: SUATU RESPONS TERHADAP FENOMENA HUSTLE CULTURE SAAT INI - Sitorus, Gideon Hasiholan (SEKOLAH TINGGI TEOLOGI DAN ENTREPRENEURSHIP PRINGGADING (STEP) SEMARANG, 2024)
The purpose of this article is to present and develop a responsive pastor leadership model amid the current hustle culture phenomenon, namely by offering a situational leadership model. This is based on the reality of pastor leadership that is identical to the application of an operational leadership model that is oriented towards monitoring the quantity of congregational attendance at services every week. This reality initiated the author's concern to construct a pastor's leadership model from operational to situational, especially when faced with the current hustle culture phenomenon. Through qualitative research methods and literature study approaches, this paper finds that pastors as leaders of God's people must be able to set aside authoritative leadership attitudes or systems. By realizing a situational leadership model that is able to dialogue the situation of the congregation filled with the complexity of daily life with the degradation of congregational attendance at church.